Machado de Assis e a denúncia da sociedade escravocrata brasileira nos contos - Rodrigues, Sophia Assis (2022)
The present research intends to develop an analysis of part of the stories of the writer Machado de Assis, great critic of the society of his time, with the main objective of discussing structural problems of our society as the contemporary sequels of the nineteenth century slavery. According to Gotlib (p.42, 2004), “the way in which short-story writer Machado represents reality brings with it a subtlety in relation to the unsaid, which opens up for ambiguities, in which various senses dialogue with each other”. Thus, the research shows tat it is necessary to make na attentive Reading of the diferente levels of Machado de Assis’ discourse to understand the political positions of the author, who was often accused of not taking a stand in relation to the problem of slavery. Aiming at achieving the target objectives, the selection of the corpus was carried out in relation to the problem under investigation, that is, short stories that best represent the way in which nineteenth-century bourgeois society behaved in the face of the problem of slavery were selected. For the analysis of the corpus, the studies by Bosi (2007), Chalhoub (2003), Duarte (2009/2013/2020), Faoro (2001) and Muricy (1988) were considered.